Community-based asthma assessment in young children: adaptations for a multicentre longitudinal study in South Asia. (July 2022) - Islam, Mohammad Shahidul; Huq, Samin; Cunningham, Steven; Schwarze, Jurgen; Islam, A.S.M.D. Ashraful; Amin, Mashal; Raza, Farrukh; Satpathy, Radanath; Rauta, Pradipta Ranjan; Ahmed, Salahuddin; Mahmood, Hana; Fernandes, Genevie; et al.
Background: Systematic assessment of childhood asthma is challenging in low- and middle-income country (LMIC) settings due to the lack of standardised and validated methodologies. We describe the contextual challenges and adaptation strategies in the implementation of a community-based asthma assessment in four resource-constrained settings in Bangladesh, India, and Pakistan. Method: We followed a group of children of age 6–8 years for 12 months to record their respiratory health outcomes. The study participants were enrolled at four study sites of the 'Aetiology of Neonatal Infection in South Asia (ANISA)' study. We standardised the research methods for the sites, trained field staff for uniform data collection and provided a 'Child Card' to the caregiver to record the illness history of the participants. We visited the children on three different occasions to collect data on respiratory-related illnesses. The lung function of the children was assessed in the outreach clinics using portable spirometers before and after 6-minute exercise, and capillary blood was examined under light microscopes to determine eosinophil levels. Results: We enrolled 1512 children, 95.5% (1476/1512) of them completed the follow-up, and 81.5% (1232/1512) participants attended the lung function assessment tests. Pre- and post-exercise spirometry was performed successfully in 88.6% (1091/1232) and 85.7% (1056/1232) of children who attempted these tests. Limited access to health care services, shortage of skilled human resources, and cultural diversity were the main challenges in adopting uniform procedures across all sites. Designing the study implementation plan based on the local contexts and providing extensive training of the healthcare workers helped us to overcome these challenges. Conclusion: This study can be seen as a large-scale feasibility assessment of applying spirometry and exercise challenge tests in community settings of LMICs and provides confidence to build capacity to evaluate children's respiratory outcomes in future translational research studies.